Maternal Triglyceride Levels in the Third Trimester and Infant Birth Weight: A Prospective Cohort Study - Fitri Afdhal; Fitrah Afdhal; Ranida Arsi; Alex Atmasubrata; Delima Ayu Sari (Jurnal Keperawatan Profesional (KEPO), 2026)
Infants born with non-optimal birth weight, either low or excessive, are at risk of experiencing growth and developmental disorders as well as long-term health problems. Maternal triglyceride levels during the third trimester play a role in lipid metabolism and are presumed to influence fetal growth. This study aimed to analyze the relationship between third-trimester maternal triglyceride levels and infant birth weight. This study employed a prospective cohort design involving 30 third-trimester pregnant women selected through consecutive sampling at an independent midwifery practice in Palembang. The study variables included maternal triglyceride levels and infant birth weight, measured using laboratory examination with the GDO-PAP method and a digital infant scale. Data were analyzed descriptively and using Pearson correlation test after logarithmic transformation of triglyceride data. The results showed that the median maternal triglyceride level was 358.3 mg/dL, while the mean infant birth weight was 3031.8 g. Pearson correlation analysis demonstrated no significant relationship between third-trimester triglyceride levels and infant birth weight (r = −0.079; p = 0.676). Third-trimester maternal triglyceride levels were not significantly associated with infant birth weight. The findings indicate that maternal triglyceride levels during the third trimester were not a determining factor of infant birth weight in this study sample.